تأثير دوافع الطلاب في إنجاز تعلمهم في مهارة الكلام بالمدرسة الإبتدائية حبيب الله بانجوانجي للسنة الدراسية 2022\2023 م: The Impact of Student Motivation on Their Achievement in Speaking Skills at Habibullah Bangunaji Elementary School for the Academic Year 2022/2023 - Mufidah, Dwi Nurul; Nurchayati, Siti (MUHIBBUL ARABIYAH: Jurnal Pendidikan Bahasa Arab, 2023)
Motivation is the potential of the individual and is the primary basis for developing personality and abilities, in which case he becomes the most dominant in determining the individual's success level. The problem of this research is (1) what are the factors that affect students' motivation in learning speech skills in Habibullah Banyuwangi primary school for the academic year 2022/2023? (2) What factor is most affected by students' motivation in learning speech skills in Habibullah Banyuwangi Primary School for the academic year 2022/2023. This research aims to (1) determine the factors that affect the motivation to learn speech skills (conversation) in class six B of the primary school Habibullah Banyuwangi. (2) Know the most dominant factors that affect the motivation to learn speech skills (conversation) in class six B of the elementary school Habibullah Banyuwangi. This research is used as the quantitative method. Use the data collection tool for the four variables to search for resolution. The community of this research is the students of class six B of the primary school Habibullah Banyuwangi, which has 27 pupils. The sample selection method in this paper is the saturated sample method. Data analysis techniques were used in this paper: validity test, stability test, and factor analysis with the help of the SPSS application. The results of the factor analysis showed that (1) factors that affect the students' learning motivation from the subject of speech skill (conversation) in class six B of the primary school Habibullah Banyuwangi is the first factor: desire (self-result 4,070). Factors II: family environment, school environment, and learning purpose (self-score 1,582). The third factor is well-off home conditions, parental benefit, and teacher motivation (self-score 1,358). (2) The most dominant factors mean the desire factor (4,070 subjective scores) or 40,697% of the total diversity. The desire factor has a 40% impacts students' learning motivation, and other factors influence the rest. Motivasi adalah potensi individu dan merupakan dasar utama untuk mengembangkan kepribadian dan kemampuan, dalam hal ini menjadi yang paling dominan dalam menentukan tingkat keberhasilan individu. Masalah penelitian ini adalah (1) faktor-faktor apa yang memengaruhi motivasi siswa dalam pembelajaran keterampilan berbicara di Sekolah Dasar Habibullah Banyuwangi untuk tahun akademik 2022/2023? (2) Faktor mana yang paling memengaruhi motivasi siswa dalam pembelajaran keterampilan berbicara di Sekolah Dasar Habibullah Banyuwangi untuk tahun akademik 2022/2023. Penelitian ini bertujuan untuk (1) menentukan faktor-faktor yang memengaruhi motivasi untuk belajar keterampilan berbicara (percakapan) di kelas enam B Sekolah Dasar Habibullah Banyuwangi. (2) Mengetahui faktor yang paling dominan yang memengaruhi motivasi untuk belajar keterampilan berbicara (percakapan) di kelas enam B Sekolah Dasar Habibullah Banyuwangi. Penelitian ini menggunakan metode kuantitatif. Menggunakan alat pengumpulan data untuk empat variabel untuk mencari solusi. Komunitas penelitian ini adalah siswa kelas enam B Sekolah Dasar Habibullah Banyuwangi, yang memiliki 27 siswa. Metode pemilihan sampel dalam makalah ini adalah metode sampel jenuh. Teknik analisis data yang digunakan dalam makalah ini: uji validitas, uji stabilitas, dan analisis faktor dengan bantuan aplikasi SPSS. Hasil analisis faktor menunjukkan bahwa (1) faktor-faktor yang memengaruhi motivasi belajar siswa dari mata pelajaran keterampilan berbicara (percakapan) di kelas enam B Sekolah Dasar Habibullah Banyuwangi adalah faktor pertama: keinginan (nilai subjektif 4,070). Faktor II: lingkungan keluarga, lingkungan sekolah, dan tujuan belajar (skor subjektif 1,582). Faktor ketiga adalah kondisi rumah yang sejahtera, manfaat orang tua, dan motivasi guru (skor subjektif 1,358). (2) Faktor yang paling dominan berarti faktor keinginan (4,070 skor subjektif) atau 40,697% dari total keragaman. Faktor keinginan memiliki dampak sebesar 40% terhadap motivasi belajar siswa, dan faktor lain memengaruhi sisanya.